2011
DOI: 10.5306/wjco.v2.i5.229
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET for hepatobiliary and pancreatic cancer: Advances and current limitations

Abstract: In Japan, the use of (18)F-fluorodeoxyglucose (FDG) positron emission tomography (PET) for some malignant tumors came to be covered by the National Health Insurance in 2002. In 2010, the health insurance coverage was expanded to all types of malignant tumors. However, since PET examination requires a large amount of capital investment, facilities at which PET is available are still limited. On the other hand, PET equipment has rapidly been introduced in large hospitals and in the diagnostic imaging centers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…The current literature includes relatively little data regarding the diagnostic role of PET/CT in patients with periampullary tumors (16)(17)(18)(19). Although the FDG-sensitivity of tumors originating from the pancreas has been reported to be between 88% and 92% (17,(19)(20)(21)(22)(23)(24)(25), there are limited findings for tumors that originate from the ampulla or distal choledochus (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current literature includes relatively little data regarding the diagnostic role of PET/CT in patients with periampullary tumors (16)(17)(18)(19). Although the FDG-sensitivity of tumors originating from the pancreas has been reported to be between 88% and 92% (17,(19)(20)(21)(22)(23)(24)(25), there are limited findings for tumors that originate from the ampulla or distal choledochus (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the clinical utility of CA 19-9 levels and PET/CT in the diagnosis and management of periampullary tumors (14)(15)(16)(17)(18)(19). Although results from these studies have been encouraging, data regarding the link between CA 19-9 levels, SUV max , and confirmed histopathological features are lacking in the current literature on periampullary tumors.…”
Section: Introductionmentioning
confidence: 99%
“…18 F]fluorodeoxyglucose ( 18 FDG PET) has become a useful tool in the evaluation of tumor lesions, particularly for pancreatic cancer, and the discovery of distant metastases [40][41][42][43]. 18 FDG is a glucose analog that is taken up aggressively by rapidly growing malignant masses, but not all hot spots are cancerous.…”
Section: Discussionmentioning
confidence: 99%
“…The role of positron emission tomography scanning (PET) is still unclear in pancreatic cancer. Chronic pancreatitis is very difficult to differentiate from pancreatic cancer and in turn it has a low specificity for detecting pancreatic cancer [35].…”
Section: Screening Toolsmentioning
confidence: 99%